ACCOUNTING INFORMATION SYSTEM REQUIREMENTS IN LIGHT OF THE GIG ECONOMY IN IRAQ (World Bulletin of Management and Law, 2022)
The era of globalization has imposed many changes in various fields of life and the countries of the world have raced to enter the global markets from the widest of their doors, everyone is trying to find the best and easiest ways to enter this new world order in various ways, which made the world more like a single village. As the advanced technological changes led to the building of a new economy based on communication network technology, it is the cart economy, which required the development of an accounting information system, which depends on information and communication technology. On the computer to track the accounting activity using information technology means, including the Internet.
Keywords: Accounting Information, E; Electronic Accounting Information System